Inhaled “Muco‐Trapping” Monoclonal Antibody Effectively Treats Established Respiratory Syncytial Virus (RSV) Infections - Morgan D. McSweeney; Sarhad Alnajjar; Alison M. Schaefer; Zach Richardson; Whitney Wolf; Ian Stewart; Pun Sriboonyapirat; Justin McCallen; Ellen Farmer; Bernadette Nzati; Sam Lord; Brian Farrer; et al. (Advanced Science, 2024)
Abstract Respiratory syncytial virus (RSV) causes substantial morbidity and mortality in infants, the immunocompromised, and the elderly. RSV infects the airway epithelium via the apical membrane and almost exclusively sheds progeny virions back into the airway mucus (AM), making RSV difficult to target by systemically administered therapies. An inhalable “muco‐trapping” variant of motavizumab (Mota‐MT), a potent neutralizing mAb against RSV F is engineered. Mota‐MT traps RSV in AM via polyvalent Fc‐mucin bonds, reducing the fraction of fast‐moving RSV particles in both fresh pediatric and adult AM by ≈20–30‐fold in a Fc‐glycan dependent manner, and facilitates clearance from the airways of mice within minutes. Intranasal dosing of Mota‐MT eliminated viral load in cotton rats within 2 days. Daily nebulized delivery of Mota‐MT to RSV‐infected neonatal lambs, beginning 3 days after infection when viral load is at its maximum, led to a 10 000‐fold and 100 000‐fold reduction in viral load in bronchoalveolar lavage and lung tissues relative to placebo control, respectively. Mota‐MT‐treated lambs exhibited reduced bronchiolitis, neutrophil infiltration, and airway remodeling than lambs receiving placebo or intramuscular palivizumab. The findings underscore inhaled delivery of muco‐trapping mAbs as a promising strategy for the treatment of RSV and other acute respiratory infections.